2019
DOI: 10.1021/acs.inorgchem.9b02483
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assembly Driven Selective Sensing of Phosphates

Abstract: A new bis-heteroleptic RuII complex (1­[PF 6 ] 2 ) with iodotriazole as the anion binding group along with the attached pyrene moiety is developed to investigate anion sensing properties and the origin of its selectivity toward a particular class of anions. Selective sensing of phosphates over other anions in both the solution and solid states by 1­[PF 6 ] 2 is clearly evident from the perturbation of the absorption band and a large degree of amplification of 3MLCT emission band in the presence of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 87 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…They may be used for sensing when the addition of an anionic species results in a disruption of this geometry and/or induces a change in optical properties [71]. Recent examples have detected anions either via coordination and interaction directly with the metal centre [72][73][74][75], or by inducing changes in the coordination environment by binding to a ligated organic group [76][77][78][79][80].…”
Section: Metal-based Chemosensorsmentioning
confidence: 99%
“…They may be used for sensing when the addition of an anionic species results in a disruption of this geometry and/or induces a change in optical properties [71]. Recent examples have detected anions either via coordination and interaction directly with the metal centre [72][73][74][75], or by inducing changes in the coordination environment by binding to a ligated organic group [76][77][78][79][80].…”
Section: Metal-based Chemosensorsmentioning
confidence: 99%
“…In their most recent extension of the phosphate‐specific aggregation phenomena, Ghosh et al. incorporated a pyrene signaling unit, leading to a maximized quantum yield of 3 % on aggregation [24] …”
Section: Introductionmentioning
confidence: 99%
“…In their most recent extension of the phosphate-specific aggregation phenomena, Ghosh et al incorporated ap yrene signaling unit, leading to am aximized quantum yield of 3% on aggregation. [24] Although Ru II complexes are potent sensing units featuring highly beneficial charge assistance of XBs, [13b, c, 20b] their twofold cationic chargem ay induce solubility issues as well as unspecific electrostatic interactions to reach charge neutrality in organic solvent mixtures. Hence, the structurally related but monocationic congener [Ir(bpy)(ppy) 2 ] + (ppy = phenylpyridine) is an attractive alternative.…”
Section: Introductionmentioning
confidence: 99%
“…moieties containing receptors have been reported for the selective recognition and sensing of phosphates. We have been systematically exploring the ruthenium complexes of pyridine triazole/iodotriazole and phenanthroline toward the development of a new class of metal complex based selective probes and extractants for phosphates. ,, In this regard, initially we developed a bis-heteroleptic Ru­(II) probe containing methyl-substituted pyridyl triazole for selective sensing of H 2 PO 4 – over HP 2 O 7 3– and other common inorganic anions through a solitary C–H···anion interaction . Then we introduced a bis-heteroleptic trinuclear Ru­(II) probe on a cyanuric acid platform for sensing of higher homologue phosphates (pyrophosphate, ADP, and ATP) over dihydrogen phosphate .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this class of probes, the basicity of anions might not govern the anion-sensing selectivity. Our recent investigation has demonstrated that the rigidification of probes via the formation of self-assembly might be responsible for the selective sensing of phosphates . In addition to hydrogen-bonding interactions, other weak interactions such as π–π stacking, anion−π interactions, etc.…”
Section: Introductionmentioning
confidence: 99%